Abstracts = Résumés (56, Fall 2005) (Labour / Le Travail, 2005)
English/French abstracts of articles in the Spring 2015 issue.
Keywords: ABSTRACTS; BIOGRAPHIES – Abstracts; Communism; Ethnicity; Working class